2022
DOI: 10.2196/39174
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Burden of Self-management: Qualitative Study Investigating the Empowering Behaviors of Patients and Informal Caregivers

Abstract: Background Patient empowerment is an important concept and a movement toward person-centered care of patients with chronic conditions. Nevertheless, to date, most research on empowered patients or informal caregivers has been conducted from a narrow clinical perspective. Such research has mainly focused on how health care professionals can empower patients to increase self-care or compliance with treatment. Research on empowered patient and informal caregiver needs and self-empowering activities is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Only a small proportion of respondents considered their organizations to provide the optimal conditions to involve patients and informal caregivers as well as support the respondents when difficult situations occurred. The questionnaire developed for this study was based on the self-empowering behaviors found by Scott Duncan et al [ 11 ]. Meeting the influencing self-empowering behaviors [ 11 ] showed that our respondents had positive attitudes towards patients (85%) and informal caregivers (83%) sharing their knowledge with other peers as mentors or communicators.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only a small proportion of respondents considered their organizations to provide the optimal conditions to involve patients and informal caregivers as well as support the respondents when difficult situations occurred. The questionnaire developed for this study was based on the self-empowering behaviors found by Scott Duncan et al [ 11 ]. Meeting the influencing self-empowering behaviors [ 11 ] showed that our respondents had positive attitudes towards patients (85%) and informal caregivers (83%) sharing their knowledge with other peers as mentors or communicators.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire developed for this study was based on the self-empowering behaviors found by Scott Duncan et al [ 11 ]. Meeting the influencing self-empowering behaviors [ 11 ] showed that our respondents had positive attitudes towards patients (85%) and informal caregivers (83%) sharing their knowledge with other peers as mentors or communicators. The respondents had encouraged this to some degree, and it existed some organizational support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations